2010
DOI: 10.7326/0003-4819-153-8-201010190-00007
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Control With Reciprocal Peer Support Versus Nurse Care Management

Abstract: Background Many health care systems face barriers to implementing resource-intensive care management programs for patients with poorly controlled diabetes. Mobilizing patients to provide reciprocal peer support may enhance care management and improve clinical outcomes. Objective To compare the effectiveness of a reciprocal diabetes peer support program (RPS) with nurse care management (NCM) in improving glycemic control in real-world clinical settings. Design Six-month parallel randomized controlled effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
357
3
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 344 publications
(372 citation statements)
references
References 50 publications
(49 reference statements)
10
357
3
2
Order By: Relevance
“…6,7 Peer health coaches have been successful at enhancing self-management and in lowering hemoglobin A1c in diabetic patients. [8][9][10][11][12] Patients' success at controlling their diabetes is not uniform. Both individuals from low socioeconomic status and from non-white racial/ethnic groups have poorer control 13 and higher diabetes related morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Peer health coaches have been successful at enhancing self-management and in lowering hemoglobin A1c in diabetic patients. [8][9][10][11][12] Patients' success at controlling their diabetes is not uniform. Both individuals from low socioeconomic status and from non-white racial/ethnic groups have poorer control 13 and higher diabetes related morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…18 In the range of peer support interventions examined in this review, individuals who were empowered to serve as mentors or were community health workers helped improve self-care behaviors among those with chronic disease conditions. 18 A study examining the effect of telephone-based reciprocal support from peers (given behavioral skills training) and periodic nurse case management on glycemic control following an initial face-to-face, group-based session among veterans with diabetes 19 found that those receiving peer support achieved A1c levels that were 0.58% lower on average than those receiving case management at 6 months. Therefore, randomized trials have demonstrated promising clinical and behavioral outcomes, with peer support interventions improving glycemic control, 20 healthy eating, patient activation, self-efficacy, and communication with physicians.…”
mentioning
confidence: 99%
“…There are significant benefits to integrating CHWs into the PCMH. Namely, clinical outcomes improve when CHWs are integrated into primary care teams [3][4][5][6][7]. Additionally, CHW-based interventions have demonstrated reduced health care use and costs for chronic care conditions [5,6,8,9].…”
Section: Purposementioning
confidence: 99%